Idiopathic Granulomatous Mastitis and History of Hypothyroidism: Intervening Data of a Prospective Multicenter Trial and Meta-Analysis of the Existing Literature: IGM and Hypothyroidism - Alipour, Sadaf; Tabatabaeian, Maryam; Nafissi, Nahid; Fattahi, Asieh Sadat; Astaraki, Shahla; Zahernia-Shahrbabaki, Zohreh; Jabbari-Nooghabi, Azadeh; Dabbagh, Najmeh; Saberi, Azin; Maajani, Khadije; Abdollahi, Azadeh; Tavakoli, Fatemeh; et al. (Archives of Breast Cancer, 2022)
Background: Idiopathic granulomatous mastitis (IGM) is a rare benign breast disease that mostly occurs in reproductive ages in parous women. Hormonal, autoimmune, and microbial causes have been implicated as causes. We carried out this prospective study to investigate the reproductive factors and underlying disease states in IGM. Methods: This study was conducted in two phases. In the first phase, we evaluated the reproductive factors, anthropometric parameters and past medical histories of participants of an ongoing multicentric clinical trial. In the second phase, we performed an extensive review of the literature for studies that had considered patients with a histologic-proven diagnosis of IGM without date limitations, and extracted the data about parity, breastfeeding, oral contraceptive pill use and past medical histories. We then carried out a meta-analysis. Results: Data of 123 patients were included. The mean age was 35.11±7.07 years, and the mean body mass index was 27.41±4.74. Overall, %93.8, 90.27% and 28.7% of patients were parous, had breastfed, and had used OCP, respectively. Hypothyroidism represented the most common (18.94%) previous medical disease. We included 89 studies in our search. Considering these studies and ours, the pooled prevalence of rates of parity, breastfeeding and oral contraceptive pill consumption were 96%, 89%, and 29%; and the pooled prevalence of hypothyroidism, diabetes and hypertension were 9%, 5% and 5%, respectively. Although not exactly comparable, these rates of hypothyroidism were higher than those reported in women in the general population (4.2% in one large study in Iran). Conclusion: Our study suggests a possible relation between a past history of hypothyroidism and IGM. We propose a study that investigates the occurrence of IGM in some large cohorts of healthy women, and the retrospective assessment of thyroid tests in the primary serum samples.